Performance and Stability of Organic Solar Cells Bearing Nitrogen Containing Electron Extraction Layers. Issue 12 (12th August 2020) - Meitzner, Rico; Essomba, Juliette; Alam, Shahidul; Anand, Aman; Engel, Nora; Fulbert, Kevin; Kuma, Krisna; Ayuyasmin, Fernanda; Islam, Md Moidul; Ugokwe, Chikezie; Schubert, Ulrich S.; Hoppe, Harald
Abstract : Charge extraction and transport layers represent an important component of organic solar cells. Many different material groups are reported for these layers. Two important classes are metal oxides and organic materials. Many of these organic materials which are used as electron extraction layers (EELs) are nitrogen containing. Therefore, it has been decided to study a broad array of—to the largest part so far not reported—amine and imine containing organic materials as EELs in organic solar cells and compare them with an archetypical metal oxide electron transport layer (ETL). It enables certain structure–property relationships to be obtained for the EELs and to understand what determines their performance to a large part. Furthermore, their effect on the stability of organic solar cells is studied and they are found to be reasonable replacements as a cheap, quickly processable, environmentally friendly, biocompatible, and biodegradable alternative as compared with ETLs. Abstract : Different amine/imine containing organic compounds are studied as electron extraction layers (EELs) in organic solar cells in regard to performance and stability. In regard to performance there is a strong connection found between content of amine groups and basicity of these groups. The best performing organic EELs work similarly well to the commonly used metal oxide TiO x .